Effect of a Selective Progesterone Receptor Modulator on Induction of Apoptosis in Uterine Fibroids In Vivo - Petr Horak; Michal Mara; Pavel Dundr; Kristyna Kubinova; David Kuzel; Robert Hudecek; Roman Chmel (International Journal of Endocrinology)
Aim. To determine if hormonal treatment induces apoptosis in uterine fibroids. Methods. Immunohistochemical examination of fibroid tissue, using avidin-biotin complex and cleaved caspase-3 antibody for detecting apoptosis, was performed in premenopausal women who underwent 12-week treatment with oral SPRM (6 patients with 5 mg and 5 patients with 10 mg of ulipristal acetate per day) or gonadoliberin agonist (GnRHa, 17 patients) and subsequent myomectomy or hysterectomy for symptomatic uterine fibroids. Ten patients with no presurgical hormonal treatment were used as controls. Results. Apoptosis was present in a significantly higher proportion of patients treated with ulipristal acetate compared to GnRHa (P=0.01) and to patients with no hormonal treatment (P=0.01). In contrast to an AI of 158.9 in SPRM patients, the mean AI was 27.5 and 2.0 in GnRHa and control groups, respectively. No statistical difference in the AI was observed between the two groups of patients treated with ulipristal acetate (5 mg or 10 mg). Conclusion. Treatment with ulipristal acetate induces apoptosis in uterine fibroid cells. This effect of SPRM may contribute to their positive clinical effect on uterine fibroids.